Pengendalian, Prinsip TQM, dan Unsur dalam Pengelolaan Mutu Sekolah - Junaidi Ana; Nurul Adha; Nurul Fajri Arifin; Nur Afif (Journal of Mandalika Literature, 2024)
Abstract: School quality control management is an important key to ensuring quality and sustainable education in every educational institution. In this context, planning, implementation,  measurement,  evaluation,  and  continuous  improvement  are  the main focus. The importance of  quality control in improving the quality of education, both  in  terms  of  student  achievement  and  teaching  effectiveness,  is  strongly emphasized. In addition, the active involvement of stakeholders, such as students, parents, teachers, and the community, is considered crucial for the success of quality control. By involving them in decision-making processes and policy implementation, schools  can  ensure  responsiveness  to  their  needs  and  expectations.  With  this approach,  schools  can  achieve  continuous  improvements  in  the  quality  of  their education in accordance with established standards. The research in this paper uses a  descriptive-qualitative  approach,  using  primary  and  supporting  literature  to review  the  existing discussion.  In conclusion,  school  quality  control  management provides  a  solid  foundation  for  achieving  optimal  academic  achievement  and provides positive benefits for all education stakeholders.